POLITIK EKOLOGI DAN EKONOMI PERTAMBANGAN DI MALUKU UTARA - Jusan Hi Yusuf; Rasty Amalia (Universitas Khairun, 2024)
The mining issue in North Moluccas has given rise to legal issues which have a negative impact on the economic and investment climate. Mining problems include forest destruction, environmental pollution, land grabbing, illegal mining, permits that are not in accordance with their intended use, and land clearing issues with miners, which then give rise to conflicts of interest with the state and local communities. These issues have been demands of society for a long time, but have not been fulfilled and resolved by the company or the government. So that conflict increases from people's attitudes of protesting to resistance. There are several factors that influence this, namely; first, the factor of centralism in mining resource policy making in the government, where the community and local government are only the recipients and implementers of the policy. Second, mining company programs towards community empowerment, namely the company's lack of concern for the social environment, especially regarding compensation related to the welfare of local communities. The results of the research show that there are issues that cause the community to protest against the mining concession policy, namely: first, the neglect of the rights of local communities in the form of compensation during mining exploitation, second, the discriminatory treatment of mining companies in the labor recruitment process. local; and third, there is post-mining environmental destruction in protected forest areas in mining areas.